Psychological and weight history variables as predictors of short‐term weight and body fat mass loss. (2nd December 2019) - Akter, Sharmin; Dawson, John A.; Kahathuduwa, Chanaka N.; Chin, Shao‐Hua; Binks, Martin
Summary: Objective: Identifying predictors of early weight loss may have value in predicting longer‐term success in weight loss programmes. This study examined if weight history variables (ie, weight cycling history [WCH], age of onset of obesity [AOO]), and preintervention Three‐Factor Eating Questionnaire (TFEQ) and Power of Food Scale (PFS) scores predicted weight loss (WL) and fat mass loss (FML) following a 3‐week calorie restriction intervention. Methods: Thirty‐two participants (19‐60 y; body mass index [BMI] 30‐39.9 kg/m 2 ) participated in a 3‐week calorie restriction intervention (1120 kcal/d) as part of a larger clinical trial with 28 completers included in the current analyses. Preintervention WCH, AOO, TFEQ, and PFS subscale scores were collected, and WL and FML were measured. Multiple linear regression analyses were performed to predict WL and FML for relevant covariates in this study. Results: WCH, AOO, preintervention TFEQ subscale scores, and PFS subscale scores did not predict WL (all P s > .08) or FML ( P s > .06) except, PFS‐food tasted scores significantly predicted WL ( r = −0.40, P = .03). Conclusion: Although these variables were not robust predictors, results for at least the PFS suggest there may be value in further exploring this measure using larger sample sizes.